Educação a distância : um estudo nas instituições públicas de educação superior no estado de Mato Grosso - Matos, Heloneide Alcantara (2016)
This dissertation, which is included on debates about higher education politics, discuss about Distance Education (DE) at higher education level, focusing towards Higher Education Institutions (HEI) from Mato Grosso state (MT). This research presents as general objective to analysis the development of distance higher education at Mato Grosso, high lighting the public institutions, regarding its conceptions about the subject, also its peculiarities and challenges. The methodological basis of the research is the descriptive-analytical method with in a qualitative approach; it was used bibliographic search about the thematic and also documentary analysis upon DE in Brazil, at MT and at the institutions involved, as well as semi-structured interview with the coordination from the Open University of Brazil and from the public HEI of MT (UFMT, UNEMAT e IFMT). The reason for choosing these institutions is due to the fact that they play a significant role among the educational spheres involved on the implantation process of the DE at MT. For the composition of the dissertation and information gathering, it became necessary to construct a logic theoretical and documentary seizure. There fore, initially it is presented the Distance Education trajectory in Brazil and at MT, on this sense it was highlighted the main legal provisions to insert DE in HEI and also academic research productions on the theme found in Brazilian graduate programs. Next, based on theoretical frameworks and specific higher education policies in distance education, the paper addresses conceptual aspects of the DE in the context of literature and documents, searching for a historical comprehension of it, especially concerning to its insertion at higher education. In order to demonstrate DE expansion at MT it was collected statistic information on the Census’s of the Higher Education from the Anísio Teixeira National Institute of Educational Studies in Brazil; on the Analytical Report from the Brazilian Association of Distance Education and on the indicators of courses/areas/joining/vacancies/ enrollment and academic organization between 1996 and 2014. The survey results showed that the development and expansion of distance education in the higher education institute occurred in accordance with the guidelines set forth in the legal documents and government programs to institutionalize distance education focused on meeting policy arrangements for certain social groups. Conclusively, it is evident that the inclusion of distance education established in public universities in Mato Grosso state occurs through the UAB system that works as a dynamic articulator of government education policy. The UAB system consists on a hybrid nature composition with decentralized responsibility and budget constraints. Nevertheless, HEI in MT have offered undergraduate courses, specialization and improvement courses that have served as a positive experience of DE in public institution to other states and other countries such as Japan.